Back Cover: Rapid Double‐Dye‐Layer Coating for Dye‐Sensitized Solar Cells using a New Method (ChemSusChem 10/2014). Issue 10 (18th September 2014) - Jung, Cho‐long; Han, Chi‐Hwan; Moon, Doo Kyung; Jun, Yongseok
<x xml:space="preserve">Abstract</x> The Back Cover picture illustrates a dye‐multi‐layered working electrode that has been prepared by applying a novel method. The new method using viscous solvents such as ethylene glycol and glycerol shortens the dye coating time to the minute scale and makes it possible to position the dye coating at a specific depth of the working electrode within minutes. This method is useful for extending sunlight harvesting by application of various dyes with different light absorption peaks. More details can be found in the Full Paper by Jung et al on page 2839 (DOI: 10.1002/cssc.201402232).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>